Functionalized iron oxide nanoparticles for controlling the movement of immune cells. Issue 17 (7th April 2015) - White, Ethan E.; Pai, Alex; Weng, Yiming; Suresh, Anil K.; Van Haute, Desiree; Pailevanian, Torkom; Alizadeh, Darya; Hajimiri, Ali; Badie, Behnam; Berlin, Jacob M.
Abstract : Coating super paramagnetic iron oxide nanoparticles with an immunostimulant, CpG oligodeoxynucleotides, dramatically increases their uptake by microglia cells. Once loaded with the nanoparticles, the microglia cells can be manipulated with magnets. Abstract : Immunotherapy is currently being investigated for the treatment of many diseases, including cancer. The ability to control the location of immune cells during or following activation would represent a powerful new technique for this field. Targeted magnetic delivery is emerging as a technique for controlling cell movement and localization. Here we show that this technique can be extended to microglia, the primary phagocytic immune cells in the central nervous system. The magnetized microglia were generated by loading the cells with iron oxide nanoparticles functionalized with CpG oligonucleotides, serving as a proof of principle that nanoparticles can be used to both deliver an immunostimulatory cargo to cells and to control the movement of the cells. The nanoparticle-oligonucleotide conjugates are efficiently internalized, non-toxic, and immunostimulatory. We demonstrate that the in vitro migration of the adherent, loaded microglia can be controlled by an external magnetic field and that magnetically-induced migration is non-cytotoxic. In order to capture video of this magnetically-induced migration of loaded cells, a novel 3D-printed "cell box" was designed to facilitate our imaging application. Analysis of cell movement velocities clearly demonstrate increased cell velocities toward the magnet. These studies represent the initial step towards our final goal of using nanoparticles to both activate immune cells and to control their trafficking within the diseased brain.